2019
DOI: 10.12998/wjcc.v7.i20.3335
|View full text |Cite
|
Sign up to set email alerts
|

Fish bone-induced myocardial injury leading to a misdiagnosis of acute myocardial infarction: A case report

Abstract: BACKGROUNDAcute chest pain (ACP) is very common among patients presenting to emergency departments. Nevertheless, ACP caused by esophageal foreign body is relatively rarely reported.CASE SUMMARYA 56-year-old man suffering from chest pain (increased pain for the last 9 h) was admitted to our hospital on October 25, 2015. After undergoing physical examination and laboratory blood testing, he was diagnosed with acute anterior myocardial infarction. Consequently, the patient underwent emergency percutaneous corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It may also assist the evaluation of complications related to this condition, such as perforation of attached structures, abscesses, mediastinitis, and aortic fistulas. 1,[5][6][7][8] We used a multidisciplinary consultative approach to evaluate the patient's clinical presentation and reached a consensus for an emergency exploratory left lateral thoracotomy to be performed. Such early intervention is strongly recommended by other reports of such critical injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may also assist the evaluation of complications related to this condition, such as perforation of attached structures, abscesses, mediastinitis, and aortic fistulas. 1,[5][6][7][8] We used a multidisciplinary consultative approach to evaluate the patient's clinical presentation and reached a consensus for an emergency exploratory left lateral thoracotomy to be performed. Such early intervention is strongly recommended by other reports of such critical injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Because it is a rare condition, esophageal perforations by foreign bodies may not be appreciated initially, and this may, of course, lead to an incorrect diagnosis and management. 5 Of paramount importance, primary evaluation of sudden-onset dysphagia with any other symptoms should include obtaining the patient's history in depth, physical and biochemical examination, and be accompanied by early imaging tests that include radiography and computed tomography (CT) scan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rare cases, fish bones may migrate to the cervical cavities and adjacent thyroid structures [10] . Several locations of vascular injury due to fish bones have been reported including the aorta, subclavian artery, common carotid artery, and superior vena cava [ 5 , [14] , [15] , [16] ]. The presentation of the foreign body inside vessels is believed to relate to 2 main mechanisms: the foreign body directly penetrates the vessel wall and the inflammatory process causes erosion of the adjacent vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…Foreign bodies with sharp nature have a tendency to migrate though tissues and lead to serious complications. Wang et al reported a case that a swallowed fish bone resulting in cardiac injury and devastating tamponade 5 . In the present case, there was a risk that the needle might penetrate the diaphragm into the abdominal cavity, which would probably cause abdominal organ damage and bleeding.…”
Section: Discussionmentioning
confidence: 99%